Rabindranath Tagore’s Contemplation of Death and Esthetics: An Observation - Md.Hasan Imam (International Journal of Advanced Science and Technology, 2020)
Rabindranath Tagore has revealed his deep contemplation about life and earth through his works. His recollection of death is not isolated from his life. Death, to him is like a prism that evaluates the human life successfully. Death has been treated as a repetitive notion of contemplation in his every literary activity especially, in prose and poetry all through his life. It is also a distance to him that manifests, cleanses as well as also disenchants the understanding of life. Death, moreover, to him is a means of observing the life through a new outlook. So the main target of this article is to represent Rabindranath Tagore’s attitude to life along with an intense viewpoint about death that explores something elementary to our comprehension of aesthetics. A discussion on the following questions is the basis of this research.